Anti N-Methyl-D-Aspartate Receptor encephalitis with ovarian teratoma: a dilemma in diagnosis - Lee, CL; Aini Amelia Zainuddin,; Abdul Kadir Abdul Karim,; Yulianty Arifuddin,; Law, Zhee Kang; Md. Isa N,; Nor Azlin Mohamed Ismail, (Faculty of Medicine, UKM Medical Centre, 2016)
We report a rare case of altered mental status in a young patient with immature ovarian teratoma. A 22-year-old woman presented with seizures, hallucination, amnesia and orofacial dyskinesia. Examination and investigation revealed an ovarian massand asalphing-oophorectomy was performed. The histopathological examination result showed an immature teratoma grade 2 with thepresence of immature primitive glial tissue. Her CSF N-Methyl-D-Aspartic acid receptor (Anti-NMDAR) antibodytest was positive. N-Methyl-D-Aspartic acid receptor antibody associated limbic encephalitis is an autoimmune antibody-mediated neuropsychiatric disorder. Resection of the tumour and immunotherapy resulted in full recovery.